(untitled) (Journal of the Association for the Study of Australian Literature, 2014)
The essay addresses the poetic dimension of David Malouf’s novels, suggesting that a poetics of possibility can be found in all his work. The poetics of possibility is a function both of Malouf’s thematic interest in the future and of his use of poetic language to draw the reader to imagine various kinds of ways of experiencing and knowing the world. The essay draws upon the philosophy of Ernst Bloch to illuminate the utopian dimension of Malouf’s work, whether in seeing the radiance of possibility in simple objects, the silent ‘presence’ at the centre of language, or the possibility of a different kind of future that Australian society might have experienced.